A Replication-Defective Herpes Simplex Virus (HSV)-2 Vaccine, HSV529, is Safe and Well-Tolerated in Adults with or without HSV Infection and Induces Significant HSV-2-Specific Antibody Responses in HSV Seronegative Individuals. (4th October 2017) - Dropulic, Lesia; Wang, Kening; Oestreich, Makinna; Pietz, Harlan; Garabedian, Doreen; Jegaskanda, Sinthujan; Dowdell, Kennichi; Nguyen, Hanh; Laing, Kerry; Koelle, David; Azose, Aaron; Hunsberger, Sally; et al.
Abstract: Background: We conducted a phase 1, randomized, double-blind, placebo-controlled trial of a replication-defective HSV-2 vaccine, HSV529 (deleted for UL5 and UL29), in 60 healthy adults aged 18 to 40 years. Methods: Subjects were enrolled in groups of 20 from 3 serogroups: HSV1+ or -/HSV2+ (group 1), HSV1+/HSV2– (group 2), and HSV1-/HSV2– (group 3). At months 0, 1, and 6, 15 subjects in each group received HSV529 intramuscularly and 5 subjects received placebo. The primary endpoint was the frequency of solicited injection site and systemic reactions from day 0 to 7 after each vaccination and unsolicited adverse events up to 6 months after the last dose. Results: 89% of vaccine recipients experienced a mild to moderate solicited injection site reaction vs. 47% of placebo recipients (P = 0.006, 95% CI 0.129, 0.676) that did not preclude additional doses. 64% of vaccine recipients experienced solicited systemic reactions vs. 53% of placebo recipients (P = 0.44, 95% CI -0.179, 0.402). Two serious adverse events occurred in 2 participants and were assessed as unrelated to HSV529 administration. Serum neutralizing antibody titers significantly increased from baseline after 3 doses of HSV529 compared with placebo in group 3 only (P < 0.001). This increase persisted up to 6 months after the third dose of vaccine (P < 0.001). Serum and vaginal antibodies to HSV2 glycoprotein D (gD) also significantly increased after 3 doses of vaccine in group 3 subjects (P < 0.001 and P = 0.012, respectively). The mean vaginal gD titer after 3 doses was about one-third of the mean serum gD titer. In addition, the vaccine induced significant levels of HSV2-specific antibody dependent cellular cytotoxicity (ADCC) after 3 doses in group 3 subjects compared with placebo (P < 0.001). Vaccine-induced CD4 T-cell responses were detected in 46%, 27%, and 36% of subjects in groups 1, 2, and 3, respectively, one month after the third dose of vaccine. CD8 T-cell responses were detected in 8%, 18%, and 14% of subjects in groups 1, 2, and 3, respectively, at the same time point. Conclusion: The HSV529 vaccine was safe, well-tolerated, and immunogenic, eliciting significant neutralizing, gD, and ADCC-mediating antibodies, and modest cellular immune responses in HSV seronegative individuals. NCT01915212 Disclosures: L. Dropulic, sanofi pasteur: Collaborator, Research support; K. Wang, sanofi pasteur: Collaborator, Research support; M. Oestreich, sanofi pasteur: Collaborator, Research support; H. Pietz, sanofi pasteur: Collaborator, Research support; D. Garabedian, sanofi pasteur: Collaborator, Research support; K. Dowdell, sanofi pasteur: Collaborator, Research support; H. Nguyen, sanofi pasteur: Collaborator, Research support; K. Laing, sanofi pasteur: Research Contractor, payment for conducting T cell assays; D. Koelle, sanofi pasteur: Research Contractor, payment for conducting T cell assays; A. Azose, sanofi pasteur: Research Contractor, Payment for conducting T cell assays; A. Chen, sanofi pasteur: Employee, Salary; L. J. Chang, sanofi pasteur: Employee, Salary; S. Phogat, sanofi pasteur: Employee, Salary